2011
DOI: 10.1215/21573698-1504517
|View full text |Cite
|
Sign up to set email alerts
|

The effect of near‐bed turbulence on sperm dilution and fertilization success of broadcast‐spawning bivalves

Abstract: Lay Abstract Many marine and some freshwater bottom‐dwelling (benthic) invertebrates broadcast their gametes into the water column where fertilization occurs. The relatively slow swimming speed and rapid dilution of sperm by water currents is thought to limit fertilization, even though species that reproduce this way can be extremely successful. We examined how water velocity and bottom roughness affected the fertilization success of zebra and quagga mussels (Dreissena polymorpha and D. bugensis) in a laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The paths of swimming sperm have been observed in the field (Babcock et al, 1994;Miller and Mundy, 2005;Quinn and Ackerman, 2011), and more typically under a microscope (Böhmer et al, 2005;Cosson et al, 1984;Evans et al, 2012;Guerrero et al, 2010a;Himes et al, 2011;Inamdar et al, 2007;Morita et al, 2006;Riffell and Zimmer, 2007;Riffell et al, 2002Riffell et al, , 2004Wood et al, 2005;Yoshida et al, 1993;Zimmer and Riffell, 2011) leading to a basic understanding of swimming patterns and parameters. Two distinct sperm behaviors have been observed: one (called loitering behavior) corresponding to sperm exposed to a chemoattractant concentration below the response threshold, and the other (called response behavior) corresponding to exposure above the threshold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paths of swimming sperm have been observed in the field (Babcock et al, 1994;Miller and Mundy, 2005;Quinn and Ackerman, 2011), and more typically under a microscope (Böhmer et al, 2005;Cosson et al, 1984;Evans et al, 2012;Guerrero et al, 2010a;Himes et al, 2011;Inamdar et al, 2007;Morita et al, 2006;Riffell and Zimmer, 2007;Riffell et al, 2002Riffell et al, , 2004Wood et al, 2005;Yoshida et al, 1993;Zimmer and Riffell, 2011) leading to a basic understanding of swimming patterns and parameters. Two distinct sperm behaviors have been observed: one (called loitering behavior) corresponding to sperm exposed to a chemoattractant concentration below the response threshold, and the other (called response behavior) corresponding to exposure above the threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Fertilization was enhanced for shear rates less than α = 1 s −1 , yet fertilization decreased in shear rates exceeding α = 1 s − 1 (Riffell and Zimmer, 2007;Zimmer and Riffell, 2011). Increases in energy dissipation rates (Denny et al, 2002), bed roughness (Quinn and Ackerman, 2011), flow velocity (Levitan et al, 1992) and turbulence (Denny and Shibata, 1989;Denny et al, 1992;Levitan and Young, 1995) have also been shown to decrease success rates. Additionally, the preference of a sperm for certain eggs within a single species (Evans et al, 2012), and viability of both the egg and sperm (Giorgi and DeMartini, 1977) can decrease actual and predicted fertilization rates.…”
Section: Introductionmentioning
confidence: 99%
“…Such flow would allow gametes to enter and be retained in areas (i.e., spaces between roughness elements) where gametes could become concentrated, as well as allowing some gametes to be transported downstream where there may encounter gametes from other individuals. In the field, however, local populations of dressenid mussels appear to exist under conditions of skimming flow, i.e., k¼10 to 15 cm and λ $ 30 cm (Quinn and Ackerman, 2011). It remains to be determined whether gamete release in benthic organisms occurs under flow conditions that enhance gamete encounter via wake interference flow (e.g., marine algae; Pearson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that an alternate choice of λ and k could have resulted in different λ/k ratios leading to isolated-roughness and wake-interference flows, where settlement would likely increase. Quinn and Ackerman (2011, 2012, 2014, found that mussel shells placed uniformly at high density on the bottom of a flow chamber led to skimming flow, in contrast to wake-interference flow observed under a low mussel-density configuration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation